2012
DOI: 10.1039/c2cp40902j
|View full text |Cite
|
Sign up to set email alerts
|

Double-chain planar D2h B4H2, C2h B8H2, and C2h B12H2: conjugated aromatic borenes

Abstract: Based upon comprehensive theoretical investigations and known experimental observations, we predict the existence of the double-chain planar D(2h) B(4)H(2)(1), C(2h) B(8)H(2)(3), and C(2h) B(12)H(2)(5) which appear to be the lowest-lying isomers of the systems at the density functional theory level. These conjugated aromatic borenes turn out to be the boron hydride analogues of the conjugated ethylene D(2h) C(2)H(4)(2), 1,3-butadiene C(2h) C(4)H(6)(4), and 1,3,5-hexatriene C(2h) C(6)H(8)(6), respectively, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 49 publications
5
47
0
Order By: Relevance
“…Both the structures of B 4 H 2 and B 6 H 2 are in agreement with the results in Ref. [13]. After the hydrogenation, for the B 3 H 2 and B 4 H 2 , the distances of B-B near H atoms increase considerably.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Both the structures of B 4 H 2 and B 6 H 2 are in agreement with the results in Ref. [13]. After the hydrogenation, for the B 3 H 2 and B 4 H 2 , the distances of B-B near H atoms increase considerably.…”
Section: Resultssupporting
confidence: 91%
“…The boron-based chemical hydrogen storage materials are quite promising since the boron atom has large coordination numbers, short covalent radius and strong directed chemical bonds with a light weight [13]. Tremendous studies have reported about this class of hydrogen storage material (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the following discussions were mainly focused on the B3LYP results. Further, relative energies for the isomers were refined using the coupled-cluster method with triple excitations (CCSD(T)) at the B3LYP structures [35,36]. Natural resonance theory (NRT) was used to calculate the bond orders and bond polarities.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…It is well accepted that the doped atoms can dramatically affect structures and properties of pure clusters. For the non-metal monovalent dopants of Bn 0/-, Bai and Li [13] reported a systematic investigation on the effect of hydrogenation of B12 0/-clusters and found that there exists a 2D−3D transition between n = 3 and 4 in B12Hn 0/-(n = 1−6), Li et al [14] reported systematic study of BnH2 0/-(n = 3-12) even electron systems. Li et al [15]in a joint experimental and theoretical study of the BnH2 -clusters for n = 8-12 have demonstrated that they have planar ladder structures.…”
Section: Introductionmentioning
confidence: 99%